Ancient Art in America. A Loan Exhibition at the Fogg Museum - Anonymus, A. (1954)
p. 21-22: Sumerian sculptures and bronzes (Nos. 54-77 A) ― 22-4: Iranian bronzes (Nos. 78-101) ― 24-5: Jewelry and minor arts (Nos. 102-122).